2019
DOI: 10.1016/j.conbuildmat.2018.12.067
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of hybrid steel fibre reinforced self compacting concrete using innovative hooked-end steel fibres under tensile stress

Abstract: 5 PO1 3AH, UK, +44 (0) 7415725441, clifford.okeh@port.ac.uk 6 7 ABSTRACT. 8The use of steel fibre hybridisation with different aspect ratios have been seen to enhance the pre and 9 post cracking response of concrete, however the invention of new innovative macro hooked ends steel 10 fibres with multiple hooks and increase in its linear length have been recently investigated. The results 11show that the new innovative macro hooked ends steel fibre with multiple hooks performed better than 12 single hooked ends … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 8 publications
(3 reference statements)
0
12
0
Order By: Relevance
“…Also, numerous reports have shown that steel fibre possesses tensile properties suitable for improving the performance of SCC [13][14][15][16][17]. Particularly, the macro-hooked ends steel fibre with multiple hooks exhibited strong impact on strength of SCC as discussed in [18]. Most of the materials were found somewhat suitable in terms of mechanical characteristics of concrete; however, an optimum objective of SCC includes that it has an excellent fresh properties regardless of its composition.…”
Section: Introductionmentioning
confidence: 99%
“…Also, numerous reports have shown that steel fibre possesses tensile properties suitable for improving the performance of SCC [13][14][15][16][17]. Particularly, the macro-hooked ends steel fibre with multiple hooks exhibited strong impact on strength of SCC as discussed in [18]. Most of the materials were found somewhat suitable in terms of mechanical characteristics of concrete; however, an optimum objective of SCC includes that it has an excellent fresh properties regardless of its composition.…”
Section: Introductionmentioning
confidence: 99%
“…From the rapid chloride permeability test (RCPT), the resistance to chloride ion penetration in the case of HM 3 is 32% higher than CC after 150 days. (6) The results show that it is suitable to use GGBS (with NSPs), RS, and CS to replace cement, river sand, and CAs in the concrete, respectively. HM 3 is considered the optimum mix for better performance, tends to fill the pores, and increases the mechanical strength of concrete.…”
Section: Discussionmentioning
confidence: 92%
“…In this project, the OPC 53 UltraTech brand is used. Tests according to IS 12269-2013 for cement are conducted and found suitable [6]. The chemical and physical characteristics of cement are placed in Tables 1 and 2.…”
Section: Methodsmentioning
confidence: 99%
“…Another possibility that has been recently explored is using combinations of fibres, the so-called fibre cocktails, in order to obtain high performance FRC with tailor made properties. Several authors have studied the mechanical properties of fibre cocktails of micro and macro steel fibres with outstanding results [ 15 , 16 , 17 ]. Fibre cocktails composed by polymer and steel fibres have been also studied, being already available in papers dealing with concrete formulations that combined polypropylene and steel fibres.…”
Section: Introductionmentioning
confidence: 99%